2005
DOI: 10.1172/jci24480
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of full effector function in vitro paradoxically impairs the in vivo antitumor efficacy of adoptively transferred CD8+ T cells

Abstract: T cell differentiation is a progressive process characterized by phenotypic and functional changes. By transferring tumor-specific CD8 + T cells into tumor-bearing mice at various stages of differentiation, we evaluated their efficacy for adoptive immunotherapy. We found that administration of naive and early effector T cells, in combination with active immunization and IL-2, resulted in the eradication of large, established tumors. Despite enhanced in vitro antitumor properties, more-differentiated effector T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

49
857
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 856 publications
(920 citation statements)
references
References 54 publications
49
857
3
1
Order By: Relevance
“…2C). These data are well in line with previous reports that exposure of antigenstimulated P14 or pmel-1 T cells to IL-2 or IL-15 generates effector or central memory-like CD8 T cells, respectively [6,[8][9][10]12]. We also noted that P14 IL-2 and P14 IL-15 cells differed in functional CD95L/Fas ligand expression since co-culture of P14 IL-2 cells and L1210 target cells expressing CD95/Fas resulted in antigen-independent cell killing whereas co-culture of the same target cells and P14 IL-15 cells had no effect (Fig.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…2C). These data are well in line with previous reports that exposure of antigenstimulated P14 or pmel-1 T cells to IL-2 or IL-15 generates effector or central memory-like CD8 T cells, respectively [6,[8][9][10]12]. We also noted that P14 IL-2 and P14 IL-15 cells differed in functional CD95L/Fas ligand expression since co-culture of P14 IL-2 cells and L1210 target cells expressing CD95/Fas resulted in antigen-independent cell killing whereas co-culture of the same target cells and P14 IL-15 cells had no effect (Fig.…”
supporting
confidence: 92%
“…The degree of specific target cell lysis and the amount of antigen-triggered IFN-g production are frequently used to predict the efficacy of CD8 T cells in vivo. However, several recent studies in the pmel-1 TCR-tg model specific for the self/tumor antigen gp100 of B16 melanoma cells indicated that antigen-stimulated CD8 T cells with a less differentiated phenotype were superior in anti-tumor activity compared with more differentiated cells [8][9][10]. In these studies, in vitro activated pmel-1 CD8 T cells were transferred into sublethally irradiated …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1-3,5-9,25,29,32,34 This perspective should promote further research and clinical translation of adoptive T cell therapy with interference of the PI3K/AKT/mTOR or Wnt-signalling pathway. 15-19,21,33 Here we show that AKT-inhibition can be used for the generation of a unique T SCM -like CD8 + T cell product for adoptive transfer.…”
Section: Discussionmentioning
confidence: 99%